EKOLOGI INFORMASI DALAM IMPLEMENTASI PERPUSTAKAAN DIGITAL DI INDONESIA : ANTARA HARAPAN DAN KENYATAAN - Susanti, Dian Arya (Universitas Pendidikan Indonesia, 2012)
Digital library services in the implementation creating an ecological metaphor of information technology perspective. An ideal ecological information will create an ideal interaction between people, technology, values and activities. In the implementation, in Indonesia, the paradigm of the library problem where it presence is still underestimated, so that the implementation of a digital library is only done half-heartedly. The existence of a state to resist change may be one of the causes of this situation. Or maybe not.